1994
DOI: 10.1002/1097-0142(19941101)74:9<2468::aid-cncr2820740913>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating cell nuclear antigen and Ki-67 in lung carcinoma. Correlation with DNA flow cytometric analysis

Abstract: Background. To study the prognosis of patients with lung carcinomas, the efficacy of proliferating cell nuclear antigen (PCNA) in ensuring both the proliferative activity defined using Ki‐67 labeling and the cell cycle data obtained using flow cytometry was determined. Methods. The authors used immunostaining to study frozen and paraffin embedded sections of 165 surgically resected lung carcinomas [squamous cell carcinoma, n = 84; adenocarcinoma, n = 62; large cell carcinoma, n = 15; small cell carcinoma, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 25 publications
5
22
1
Order By: Relevance
“…Immunohistochemistry used to reveal Ki-67 protein was not always performed with the same antibody: clone Mib-1 in the majority of the studies (Costes et al, 1995;Bohm et al, 1996;Fontanini et al, 1996;Bellotti et al, 1997;Ishida et al, 1997;Komaki et al, 1998;Dazzi et al, 1999;Dingemans et al, 1999Dingemans et al, , 2001Santinelli et al, 1999;Cagini et al, 2000;Demarchi et al, 2000;Hommura et al, 2000;Nguyen et al, 2000;Shiba et al, 2000Shiba et al, , 2001van de Vaart et al, 2000;Ferreira et al, 2001;Hayashi et al, 2001;Puglisi et al, 2001Puglisi et al, , 2002Ramnath et al, 2001;Tsoli et al, 2001;Minami et al, 2002;Rigau et al, 2002), antibodies coming from a firm selling several clones but without mention of the clone used (Hayashi et al, 1993;Pence et al, 1993;Kawai et al, 1994;Giaccone et al, 1995;Pujol et al, 1996;Mehdi et al, 1998;Soomro et al, 1998;Carbognani et al, 2002); any mention of the antibodies used (Tungekar et al, 1991;Harpole Jr et al, 1995Giatromanolaki et al, 1996a, b;D'Amico et al, 1999D'Amico et al, , 2000Carvalho et al, 2000;Pelosi et al, 2001)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemistry used to reveal Ki-67 protein was not always performed with the same antibody: clone Mib-1 in the majority of the studies (Costes et al, 1995;Bohm et al, 1996;Fontanini et al, 1996;Bellotti et al, 1997;Ishida et al, 1997;Komaki et al, 1998;Dazzi et al, 1999;Dingemans et al, 1999Dingemans et al, , 2001Santinelli et al, 1999;Cagini et al, 2000;Demarchi et al, 2000;Hommura et al, 2000;Nguyen et al, 2000;Shiba et al, 2000Shiba et al, , 2001van de Vaart et al, 2000;Ferreira et al, 2001;Hayashi et al, 2001;Puglisi et al, 2001Puglisi et al, , 2002Ramnath et al, 2001;Tsoli et al, 2001;Minami et al, 2002;Rigau et al, 2002), antibodies coming from a firm selling several clones but without mention of the clone used (Hayashi et al, 1993;Pence et al, 1993;Kawai et al, 1994;Giaccone et al, 1995;Pujol et al, 1996;Mehdi et al, 1998;Soomro et al, 1998;Carbognani et al, 2002); any mention of the antibodies used (Tungekar et al, 1991;Harpole Jr et al, 1995Giatromanolaki et al, 1996a, b;D'Amico et al, 1999D'Amico et al, , 2000Carvalho et al, 2000;Pelosi et al, 2001)…”
Section: Discussionmentioning
confidence: 99%
“…In total, 42 studies published between 1991 and 2002 were selected for this systematic review (Tungekar et al, 1991;Hayashi et al, 1993;Pence et al, 1993;Kawai et al, 1994;Costes et al, 1995;Giaccone et al, 1995;Harpole, Jr et al, 1995Bohm et al, 1996;Fontanini et al, 1996;Giatromanolaki et al, 1996a, b;Pujol et al, 1996;Bellotti et al, 1997;Ishida et al, 1997;Komaki et al, 1998;Mehdi et al, 1998;Soomro et al, 1998;D'Amico et al, 1999D'Amico et al, , 2000Dazzi et al, 1999;Dingemans et al, 1999Dingemans et al, , 2001Santinelli et al, 1999;Cagini et al, 2000;Carvalho et al, 2000;Demarchi et al, 2000;Hommura et al, 2000;Nguyen et al, 2000;Shiba et al, 2000Shiba et al, , 2001van de Vaart et al, 2000;Ferreira et al, 2001;Hayashi et al, 2001;Pelosi et al, 2001;Puglisi et al, 2001Puglisi et al, , 2002Ramnath et al, 2001;Tsoli et al, 2001;Carbognani et al, 2002;Minami et al, 2002;Rigau et al, 2002). Five were excluded because an identical patients cohort was used in another selected publication (references excluded/includ...…”
Section: Studies Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCNA is a nuclear protein acting as a cofactor for DNA polymerase delta (Mathews et al, 1984). PCNA has been used as a proliferation and prognostic marker in a variety of malignancies, including lung tumors (Kawai et al, 1994) and it is an important prognostic factor of clinical outcome in patients with NSCLC (Volm and Koomagi, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…26 They investigated a relationship between PCNA and sex, age, tumor stage, survival, histologic type, degree of cell differantion and cellularity. They found that there was concordance between PCNA and clinical stage, cellularity and DNA content.…”
Section: Discussionmentioning
confidence: 99%